Improving EFL Students’ English Proficiency through Pair Interaction within a Lesson Study Framework - Suhartina R; Kaharuddin; Fien Pongpalilu (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Non-English language students still show underdeveloped communication skills, especially in speaking. This has an impact on their poor English language skills. This study aims to analyze the effectiveness of Pair interaction within a learning lesson framework to improve EFL students' English language skills. This study highlights six main language domains: grammar, comprehension, reading, writing, listening, and speaking. This study used a quantitative pre-experimental design using a one-group pre-test-post-test model. The subjects of this study were 30 second-semester students from the Accounting Study Program. The selection was purposively based on their study status and initial English placement test results. Data collection methods used observation, interviews, and tests. The research instruments were test questions and questionnaires. Data analysis techniques used descriptive statistics, t-tests, and multiple regression analysis. The study's t-test results showed significant improvements in all domains, especially grammar, vocabulary, and speaking. Regression analysis showed the third domain as the strongest predictor of overall improvement. These findings underline the importance of pair interaction as a collaborative strategy to encourage comprehensive language skill development, increase communication confidence, and build students' active participation in English learning. This intervention is considered adequate in EFL-based English learning through reflection and collaboration.